Blood type gene locus has no influence on ACE association with Alzheimer's disease - Braae, Anne; Medway, Christopher; Carrasquillo, Minerva; Younkin, Steven; Kehoe, Patrick G.; Morgan, Kevin (Elsevier, 2015)
The ABO blood group locus was recently found to contribute independently as well as via interactions with ACE gene variation to plasma levels of angiotensin converting enzyme (ACE). Variation in ACE has also previously been implicated as conferring susceptibility for Alzheimer’s disease (AD), but has also been proposed to confer risk via interactions with other as yet unknown genes. More recently, larger studies have not supported ACE as a risk factor for AD, while the role of ACE pathway in AD has come under increased levels of scrutiny with respect to various aspects of AD pathology and possible therapies. We explored the potential combined involvement of ABO and ACE variation in the genetic susceptibility of 2067 AD cases compared to 1376 non-demented elderly. Including the effects of ABO haplotype did not provide any evidence for the genetic association of ACE with AD.